CD40L induces functional tunneling nanotube networks exclusively in dendritic cells programmed by mediators of type-1 immunity - Zaccard, Colleen R. (J Immunol, 2014)
The ability of dendritic cells (DC) to mediate CD4(+) T cell help for cellular immunity is guided by instructive signals received during DC maturation, and the resulting pattern of DC responsiveness to the Th signal, CD40L. Furthermore, the professional transfer of antigenic information from migratory DC to lymph node-residing DC is critical for the effective induction of cellular immune responses. Here we report that, in addition to their enhanced IL-12p70 producing capacity, human DC matured in the presence of inflammatory mediators of type-1 immunity (DC1) are uniquely programmed to form networks of tunneling nanotube-like structures in response to CD40L-expressing Th cells or recombinant CD40L. This immunologic process of DC ‘reticulation’ facilitates intercellular trafficking of endosome-associated vesicles and Ag, but also pathogens such HIV-1, and is regulated by the opposing roles of IFN-γ and IL-4. The initiation of DC reticulation represents a novel helper function of CD40L and a superior mechanism of intercellular communication possessed by DC1, as well as a target for exploitation by pathogens to enhance direct cell-to-cell spread.